Kallikrein-related peptidases 4, 5, 6 and 7 regulate tumour-associated factors in serous ovarian cancer. Issue 7 (2nd October 2018) - Wang, Ping; Magdolen, Viktor; Seidl, Christof; Dorn, Julia; Drecoll, Enken; Kotzsch, Matthias; Yang, Feng; Schmitt, Manfred; Schilling, Oliver; Rockstroh, Anja; Clements, Judith; Loessner, Daniela
Abstract Background Tissue kallikrein-related peptidases 4, 5, 6 and 7 (KLK4–7) strongly increase the malignancy of ovarian cancer cells. Deciphering their downstream effectors, we aimed at finding new potential prognostic biomarkers and treatment targets for ovarian cancer patients. KLK4–7-transfected (OV-KLK4–7) and vector-control OV-MZ-6 (OV-VC) ovarian cancer cells were established to select differentially regulated factors. Methods With three independent approaches, PCR arrays, genome-wide microarray and proteome analyses, we identified 10 candidates (MSN, KRT19, COL5A2, COL1A2, BMP5, F10, KRT7, JUNB, BMP4, MMP1). To determine differential protein expression, we performed western blot analyses, immunofluorescence and immunohistochemistry for four candidates (MSN, KRT19, KRT7, JUNB) in cells, tumour xenograft and patient-derived tissues. Results We demonstrated that KLK4–7 clearly regulates expression of MSN, KRT19, KRT7 and JUNB at the mRNA and protein levels in ovarian cancer cells and tissues. Protein expression of the top-upregulated effectors, MSN and KRT19, was investigated by immunohistochemistry in patients afflicted with serous ovarian cancer and related to KLK4–7 immunoexpression. Significant positive associations were found for KRT19/KLK4, KRT19/KLK5 and MSN/KLK7. Conclusion These findings imply that KLK4–7 exert key modulatory effects on other cancer-related genes and proteins in ovarian cancer. These downstream effectors of KLK4–7, MSN and KRT19 may represent important therapeutic targets in serous ovarian cancer.